The Evaluation of the Awareness, Attitude and Practice of the Elderly Toward Self-Medication: A Cross-Sectional Study - Heidari, Mohammad; Borujeni, Mansureh Ghodusi; Ghafourifard, Mansour; Sheikhi, Rahim Ali (Drug Research, 2018)
Introduction The prevalence of various diseases in the elderly has increased the use of drugs, which is coupled with age-related physiological changes and places the elderly at risk for multiple side effects. The present study aimed to determine awareness, attitudes and practices of elderly towards self-medication.Materials and Methods The sample included 300 participants over 60 years under any of the health centers in urban and rural areas of Abadeh city, who were selected based on stratified random sampling method. In order to collect data, the questionnaire including demographic information, awareness, attitude and performance of the elderly and the checklist of drug intractable consumption.Results Based on the results, 76% of the elderly reported drug consumption. Regarding lifestyle, the average score of the elderly’s awareness for the elderly who lived with and without families were 78.6±14.2 and 69.2±13.6, respectively. In other words, a significant difference was observed between these two groups. In addition, there was a significant between the elderly’s performance score with and without family members about the self-medication (p=0.001).Conclusion Considering the increase in self-medication among the elderly, adherence to prescription criteria for drug among this age group is recommended. Finally, designing and implementing various educational programs in health education center is necessary for the elderly and their families for the purpose of improving awareness and practice.
Keywords: Self-medications; elderly; drug delivery